Treatment of splanchnic artery aneurysms – single center results and experience - Kostić, Ognjen; Dučić, Stefan; Matejević, David; Roganović, Andrija; Davidović, Lazar (Vojnosanitetski pregled, 2026)
Background/Aim. Visceral artery aneurysms (VAAs) are rare but potentially life-threatening conditions. With the increasing availability of diagnostic and therapeutic options, there is a growing need to determine the optimal treatment approach–endovascular (EV) vs. open surgical (OS) reconstruction. The aim of this study was to analyze treatment outcomes in patients with VAA at a single center and compare the efficacy of EV and OS approaches. Methods. The study included 27 OS (the OS group) or EV (the EV group) interventions for VAA, performed at our institution from January 2010 to November 2023, on 27 patients, 13 males and 14 females, with a mean age of 57 ± 13 years. Treatment decisions were reached by a multidisciplinary team of a vascular surgeon, an anesthesiologist, and an interventional radiologist. Results. Out of the 27 patients, 9 were treated in the emergency setting, with 6 of them having ruptured aneurysms. The most common was a splenic artery aneurysm, 50.0% of all VAAs. Thirteen patients underwent EV reconstruction, one patient underwent a hybrid approach, and 13 patients had OS reconstruction. Technical success was 24/27 or 88.9%. Eleven patients were treated by coil embolization, while two were treated with the implantation of a covered stent. In the EV group, mortality was nil. In 14 patients, OS treatment was performed with 9 VAA resections and arterial reconstructions (7 with Dacron graft, 1 with polytetrafluoroethylene graft, and 1 with autovenous graft), with 2 splenectomies and 3 aneurysm exclusions. Two patients died intraoperatively due to severe bleeding, and one after the procedure because of intestinal ischemic complications. Mean duration of hospitalization after OS or EV procedure was 7.43 and 4.92 days, respectively. Conclusion. Treating patients using the EV approach is safe, with less invasiveness and shorter hospital stays, suitable for elective and emergency cases when technically feasible. OS remains a reliable option at high-volume centers, particularly for complex cases unsuitable for EV approaches or in low-risk patients. Treatment decision should be guided by VAA characteristics (size, symptoms, location, morphology), patient comorbidities, and specific clinical context, such as prior abdominal surgeries.
Keywords: aneurysm; arteries; endovascular procedures; serbia; treatment outcome; vascular surgical procedures.